Design and digital implementation of power control strategy for grid connected photovoltaic inverter - Linda Hassaine; Mohamed Rida Bengourina (Institute of Advanced Engineering and Science, 2019)
This paper presents the optimization design and a detailed implementation in FPGA (Field-Programmable Gate Array) of a power control strategy. This strategy is based on the phase shift angle of the inverter output voltage with respect to the grid voltage and DSPWM (Digital Sinusoidal Pulse Width Modulation) patterns “Phase shift angle-DSPWM” for an inverter for photovoltaic system connected to the grid. The proposed control can synchronize a sinusoidal inverter output current with a grid voltage and control the power injected into the grid. Detailed development of a digital controller with lower hardware and computation requirement is proposed. Description on the digital implementation of the A/D converter, the PI compensator, the phase shift and the DPWM, is provided. This digital control exhibit simplicity, reduction of the memory requirements and power calculation for the control. The functional structure of this system with digital control has been validated with simulations and experimental results.